Low Humoral Immune Response and Ineffective Clearance of SARS-Cov-2 in a COVID-19 Patient With CLL During a 69-Day Follow-Up - Ye, Xingnong; Xiao, Xiaofang; Li, Bin; Zhu, Weigang; Li, Youjiang; Wu, Jianguo; Huang, Xin; Jin, Jingxia; Chen, Dan; Jin, Jie; Huang, Jian (Frontiers in Oncology, 2020)
Background: A recent outbreak of severe acute respiratory syndrome corona virus 2 (SARS-Cov-2), which began in Wuhan, China, with a high level of human-to-human transmission has been reported. There are limited data available on Corona virus Disease 2019 (COVID-19) patients with hematological malignancies for more than sixty days of follow-up. This study describes the clinical characteristics, including multiple recurrences of COVID-19, in a patient with chronic lymphocytic leukemia (CLL) during 69 days of follow-up. Case presentation: A 72-year-old female was admitted to hospital isolation after being infected with COVID-19 as part of a family cluster on January 30, 2020.Apart from SARS-Cov-2 virus infection, laboratory results revealed lymphocytosis of uncertain etiology and abnormal distribution of T lymphocytes. On blood smears, small blue lymphocytes with scant cytoplasm were observed, and the presence of high levels of circulating clonal B cells was also demonstrated by flow cytometry. The patient was diagnosed withCOVID-19 and CLL. Among her family members, she had the highest viral loads and the fastest progression on lung injury and developed severe pneumonia. Serological results showed she had both 2019-nCoV-specific IgM and IgG antibodies; however, only IgG antibodies were detected in her husband’s plasma. Results: A combination regimen of antiviral therapy and high-dose intravenous immunoglobulin (IVIG) in the early stage seemed to be effective for treating CLL and SARS-Cov-2infection.Because of the low humoral immune response, the CLL patient could not effectively clear the SARS-Cov-2 infection and suffered from recurrence twice during the 69-day follow-up. Conclusion: In CLL, a neoplastic antigen-specific B cell clone proliferates, and the progeny cells accumulate and outgrow other B cells, leading to immune deficiency. Considering the low humoral immune response and ineffective clearance of SARS-Cov-2 in CLL patients, the follow-up and home quarantine period should be extended. We need further studies to clarify suspending or continuing CLL therapy during COVID infection. For those patients who are prone to progression to severe disease, administering humoral immunity therapies can help to prevent disease progression and quickly meet the cure criteria.